2020
DOI: 10.2459/jcm.0000000000001097
|View full text |Cite
|
Sign up to set email alerts
|

Bridge to heart transplantation in patients with cardiogenic shock: a 20-year experience with two different surgical strategies

Abstract: Aims We aimed to describe how treatment of patients in cardiogenic shock bridged to heart transplantation with mechanical circulatory support, using either biventricular assist devices (BVADs) or extracorporeal life support (ECLS), has evolved in the last 20 years in our centre. Methods Since 1998, 72 patients with refractory heart failure and indication for heart transplantation have received mechanical circulatory support: 40 had an ECLS system and 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Other conditions that were reported to be risk factors for death are infection, high levels of lactate, and liver dysfunction [5,[6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Outcomes Of Btt With Ecmomentioning
confidence: 99%
See 1 more Smart Citation
“…Other conditions that were reported to be risk factors for death are infection, high levels of lactate, and liver dysfunction [5,[6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Outcomes Of Btt With Ecmomentioning
confidence: 99%
“…On the other hand, patients supported with ECMO who could not be weaned and have major risk factors may warrant consideration for an alternative to HT, such as LVAD implantation. In fact, it has been argued that perhaps a strategy of transitioning ECMO supported patients to durable MCS may provide the stabilization required to guarantee better post HT outcomes and more judicious use of transplanted hearts [9,19], but limited and controversial evidence does not permit to generate recommendations.…”
Section: Listing Ecmo Patientsmentioning
confidence: 99%
“…The Swedish evaluation of left ventricular assist device (SweVAD) study will provide further data regarding LVAD implantation as the destination therapy in patients with advanced HF ineligible for heart transplantation 72 . Biventricular assist device may have a role in selected patients, 73 but further research is needed.…”
Section: Advanced Heart Failurementioning
confidence: 99%
“…ESRD alone increased the risk of readmission within 30 days [7]. A study evaluated the use of extracorporeal life support (ECLS) or biventricular device (BiVAD) in patients in cardiogenic shock bridged to heart transplantation and found that patients with extracorporeal support had higher rates of renal failure (P = 0.02) compared to the BiVAD patients [32].…”
Section: Outcomes With Lvad In End-stage Renal Diseasementioning
confidence: 99%